Design, Modeling, and Feasibility Analysis of Rotary Valve for Internal Combustion Engine - Wenbo Dong; Vishwas N. Bedekar (Journal of Combustion)
There have been several studies focused on improving the efficiency of internal combustion engines using various techniques such as better design, better materials, and regenerative technologies. Recently, in 2016, Toyota reported 40% gas engine efficiency with their Prius model; however, there remains a lot more room for improvement towards the theoretical maximum value of 73% using the Carnot theorem. In this research, we present a freshly designed valvetrain that has the potential to improve the efficiency of a known conventional valve designed engine. The goal of this research was to prove the feasibility and significance of the new valve design. This research developed a simulation model of the new valve design and produced its physical property data. The data of the new design were compared to the conventional poppet valve design with respect to several parameters to discuss its working principle and advantages over the conventional valve mechanism. Modeling was performed using Python programming to predict the valve-opening mechanism. The design of experiments was setup to control and tune different parameters accordingly within the reasonable range of engine speed, viz., 1000–6000 rpm to simulate various working conditions. The maximum opening area for the rotary valve is calculated to be 0.795 sq.in which is smaller than the poppet valve’s area of 1.315 sq.in. However, under an example of 2900 rpm, the rotary valve was able to remain fully opened with constant efficiency of about 54% from 40 to 160 degrees of the crankshaft angle. While the poppet valve can achieve 88% efficiency at 90 degrees of the crankshaft angle and the efficiency significantly drops on either side of the maxima, the authors believe that this research would help explore improvements in the performance of a combustion cycle due to the novel rotary valve design that is investigated in this paper.